Subtitling Virtual Reality into Arabic: Eye Tracking 360-Degree Video for Exploring Viewing Experience - El Mehdi Ibourk (14585247) (2019)
The recent years have witnessed the emergence of new approaches in filmmaking including virtual reality (VR), which is meant to achieve an immersive viewing experience through advanced electronic devices, such as VR headsets. The VR industry is oriented toward developing content mainly in English and Japanese, leaving vast audiences unable to understand the original content or even enjoy this novel technology due to language barriers. This paper examines the impact of the subtitles on the viewing experience and behaviour of eight Arab participants in understanding the content in Arabic through eye tracking technology. It also provides an insight on the mechanism of watching a VR 360-degree documentary and the factors that lead viewers to favour one subtitling mode over the other in the spherical environment. For this end, a case study was designed to produce 120-degree subtitles and Follow Head Immediately subtitles, followed by the projection of the subtitled documentary through an eye tracking VR headset. The analysis of the eye tracking data is combined with post-viewing interviews in order to better understand the viewing experience of the Arab audience, their cognitive reception and the reasons leading to favour one type of subtitles over the other.  Other information  Published in: Lebende Sprachen License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1515/les-2019-0016